On the Verbal Expression of Emotions: Language and Emotion Interplays - Stepanyan, Ani (Armenian Folia Anglistika, 2014)
In pre-historic times people used to communicate with each other through grunts, barks and roars. They gradually developed an elaborate set of sounds to express their emotions and convey their messages. Now it is the systematic use of language that differentiates human beings from animals. The interpersonal communication of emotional states is fundamental to everyday verbal interactions, and the way these emotions are expressed and understood is important in cross-cultural and interpersonal relationships. The verbal descriptions of emotional states can provide quite precise information about different forms of emotions.